2017
DOI: 10.1038/leu.2017.233
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2V617F-bearing vascular niche promotes clonal expansion in myeloproliferative neoplasms

Abstract: The acquired kinase mutation JAK2V617F plays a central role in myeloproliferative neoplasms (MPNs). However, the mechanisms responsible for the malignant hematopoietic stem/progenitor cell (HSPC) expansion seen in patients with MPNs are not fully understood, limiting the effectiveness of current treatment. Endothelial cells (ECs) are an essential component of the hematopoietic niche, and they have been shown to express the JAK2V617F mutation in patients with MPNs. We show that the JAK2V617F-bearing vascular ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 62 publications
6
58
0
Order By: Relevance
“…Contrary to what we observed previously in a direct transplantation experiment in which Pf4 + FF1 + marrow cells were transplanted into WT recipients and thrombocytosis developed 8 weeks after transplantation , no significant difference in blood cell count, spleen weight, or total femoral cell count was observed between the Pf4 + FF1 + marrow recipients and control marrow recipients in the competitive transplantation experiment performed here. Such different phenotypes between direct and competitive marrow transplantation were also observed in another JAK2V617F‐positive MPN murine model in which the JAK2V617F mutation is expressed in all hematopoietic cells (including HSPCs) and ECs. Considering that competition between normal cells and cancer cells is a major factor for cancer initiation , the difference in Pf4 + FF1 + marrow donor chimerism (i.e., ∼60% in the competitive transplant assay reported here vs. ∼95% in the direct transplant assay ) could contribute to the different phenotype we have observed.…”
Section: Discussionmentioning
confidence: 55%
“…Contrary to what we observed previously in a direct transplantation experiment in which Pf4 + FF1 + marrow cells were transplanted into WT recipients and thrombocytosis developed 8 weeks after transplantation , no significant difference in blood cell count, spleen weight, or total femoral cell count was observed between the Pf4 + FF1 + marrow recipients and control marrow recipients in the competitive transplantation experiment performed here. Such different phenotypes between direct and competitive marrow transplantation were also observed in another JAK2V617F‐positive MPN murine model in which the JAK2V617F mutation is expressed in all hematopoietic cells (including HSPCs) and ECs. Considering that competition between normal cells and cancer cells is a major factor for cancer initiation , the difference in Pf4 + FF1 + marrow donor chimerism (i.e., ∼60% in the competitive transplant assay reported here vs. ∼95% in the direct transplant assay ) could contribute to the different phenotype we have observed.…”
Section: Discussionmentioning
confidence: 55%
“…MPN stem cell expansion and disease relapse after marrow transplantation) in vitro in our previous studies. 19,24,25 When wild-type or JAK2V617Fmutant Lin -cKit + HSPCs were seeded on a monolayer of lung endothelium mixed from 0-100% JAK2V617Fmutant ECs, we found that the presence of as low as 10% mutant ECs in the mixed monolayer promoted the expansion of mutant HSPCs in preference to wild-type HSPCs. (Figure 5) This finding was not surprising to us, since as few as 2% mutant blood cells can produce >2-fold increase of heart disease in individuals with CHIP.…”
Section: Jak2v617f-mutant Ecs Promote the Expansion Of Jak2v617f Hspcmentioning
confidence: 87%
“…As we have reported, Tie2FF1 mice develop a myeloproliferative phenotype with leukocytosis, thrombocytosis, significant splenomegaly, and greatly increased numbers of hematopoietic stem cells by 8 wk of age. [23][24][25] We noticed that there was an increased incidence of sudden death during performance of minor procedures (e.g. submandibular bleeding) in Tie2FF1 mice, especially after 20 wk of age ( Figure 1A).…”
Section: Development Of Spontaneous Heart Failure With Increased Riskmentioning
confidence: 99%
“…By 18 weeks post-transplant, Tie2 + /FF1 + recipients of an equal mixture of Tie2 + /FF1 + and wild-type cells developed a profound MPN phenotype with neutrophilia, thrombocytosis, and moderate splenomegaly. 11 Quantitative evaluation of the marrow HSC compartment at that time revealed significant increases in JAK2 V617F CD150 + CD48 − cells, a population of cells highly enriched in HSCs (ß20% display long-term repopulating capacity), in Tie2 + /FF1 + recipients compared with control recipients. In contrast, and somewhat surprisingly, control recipients (with the normal stem cell niche) of an equal mixture of Tie2 + /FF1 + and normal cells had mostly normal blood cell counts, and there were no significant differences between the numbers of normal and mutant CD150 + CD48 − cells in the marrow of the mice.…”
Section: The Jak2 V617f Vascular Niche Promotes Jak2 V617f -Mutant CLmentioning
confidence: 99%
“…In contrast to the five Tie2 + /FF1 + recipients with full donor engraftment, the seven mice with mixed chimerism developed neutrophilia, thrombocytosis, splenomegaly, and mutant HSC expansion, similar to what we observed in the primary Tie2 + /FF1 + JAK2 V617F -mutant mice. 3,11 Thus, JAK2 V617F HSCs in Tie2 + /FF1 + mice were relatively protected from an otherwise lethal dose of irradiation administered during preparation for marrow transplantation. In essence, the presence of JAK2 V617F generated a model of disease refractory to what should have been curative transplantation.…”
Section: The Jak2 V617f -Positive Ecs Protect Jak2 V617f Hscs From Ramentioning
confidence: 99%